2004
DOI: 10.2307/3473169
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Chimpanzees, Tools, and Termites from the Congo Basin

Abstract: The tool-using behaviors of wild chimpanzees comprise the most impressive assemblages and flexible repertoires of nonhuman material culture. We expand knowledge of the breadth and complexity of tool use in this species by providing the first descriptions of the form and function of two distinct tool sets used by chimpanzees in preying upon termites within the forests of the Goualougo Triangle, Republic of Congo. Further, we report the first application of remote video monitoring technology to record wild chimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
96
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 0 publications
3
96
0
3
Order By: Relevance
“…Recent experimental evidence indicates a conformity bias that has the potential to strengthen the effect of the culturally shaped niche to which each developing individual is exposed . Among both human and nonhuman societies, such culturally constructed niches may be instantiated not only materially, as in the case of accumulations of useful tools at chimpanzee termiting sites (Sanz et al 2004), but in social conventions. For example, Perry et al (2003a;2003b) have described several types of intimate social interactions and games, including bizarre actions like resting one's fingers deep in companions' mouths and noses, that have the hallmarks of local conventions among different communities of wild capuchin monkeys.…”
Section: R22 Further Parallels With Evolutionary Biologymentioning
confidence: 99%
“…Recent experimental evidence indicates a conformity bias that has the potential to strengthen the effect of the culturally shaped niche to which each developing individual is exposed . Among both human and nonhuman societies, such culturally constructed niches may be instantiated not only materially, as in the case of accumulations of useful tools at chimpanzee termiting sites (Sanz et al 2004), but in social conventions. For example, Perry et al (2003a;2003b) have described several types of intimate social interactions and games, including bizarre actions like resting one's fingers deep in companions' mouths and noses, that have the hallmarks of local conventions among different communities of wild capuchin monkeys.…”
Section: R22 Further Parallels With Evolutionary Biologymentioning
confidence: 99%
“…Recently, Sanz et al (13) sought to refute the notion that the behaviors cannot be considered cultural because they do not show signs of the ratchet effect. They suggested that certain behavioral patterns shown by some populations of wild chimpanzees have become more elaborate through time (e.g., termite-fishing strategies).…”
mentioning
confidence: 99%
“…The chimpanzees never arrived at the site of a subterranean nest without bringing such a stick with them, unless one had previously been left at the site. And this was true even though the nearest appropriate tree was tens of meters away in the forest, from which point the nest site could not be seen (59). Such behavior in humans would involve imagination of the target together with mental rehearsal of the actions needed to acquire it, which would both remind and motivate one to deviate from one's path to find an appropriate species of tree.…”
Section: Inability Tomentioning
confidence: 99%